PERILAKU REMAJA PUTRI TENTANG PENATALAKSANAAN DAN PENCEGAHAN KEPUTIHAN DI PONDOK PESANTREN PUTRI UMMU SULAIM PEKANBARU TAHUN 2018 - Sari, Rina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Vaginal discharge is excessive fluid from the genitals (vagina). This can be prevented bydrying the skin with a towel or tissue when sweating or after bowel movements, in additionto using clean, dry underwear, avoiding wearing tight underwear and frequently changingpads when it comes to months. In order to avoid infection from microorganisms that comefrom the anus or rectum is recommended to cebok from the front toward the rear. Theresearcher aims to know the behavior of young women about the implementation andprevention of whiteness in Pondok Pesantren Putri Ummu Sulaim Pekanbaru Year 2018.This research type is quantitative, with descriptive design using the primary data obtainedfrom the questionnaire. The number of respondents was 113 respondents. By proportionalstratification rondom sampling technique. Data obtained by presented in frequencydistribution table. Data processing with editing, coding, and tabulating. The result of theresearch is from the knowledge of adolescent that the majority have low knowledge asmuch as 60 (53%) of respondents, majority have positive nature as many as 60 (53%)respondents, and majority do not do management and prevention of whiteness as much 58(51,3%) reaponden. For respondents expected to know information about the managementand prevention of whiteness for themselves or around the environment so that it can applyas the hand extension of health workers and can provide knowledge about managementand prevention of whiteness.Keyword : Knowledge, Attitude, Action, Teenagers, Management And Prevention WhitishPENDAHULUANKesehatan reproduksi remaja adalah kesehatan remaja secara fisik, mental dankesejahteraan sosial secara utuh pada semua hal yang berhubungan dengan sistem danfungsi serta proses reproduksi dan bukan hanya kondisi yang bebas dari penyakit dankecacatan (BKKBN, 2008).Menurut WHO (World Health Organization) dalam Marmi (2013), remaja adalahmereka yangberusia 10-19 tahun. Sementara dalam terminologi lain PBB (PerserikatanBangsa Bangsa) menyebutkan anak muda (youth) untuk mereka yang berusia 15-24tahun.Ini kemudian disatukan dalam sebuah terminology kaum muda (young people) yangmencakup 10-24 tahun.Menurut Puduastuti dalam Kurniawati (2014), setiap remaja memperoleh hak yangsama dalam menjaga kesehatan reproduksinya. Organ reproduksi merupakan organ tubuhyang sensitif dan memerlukan perawatan khusus. Pengetahuan dan perawatan yang baikdalam menjaga kebersihan organ reproduksi dapat memelihara kesehatan reproduksi.Organ reproduksi dapat terkena sejenis jamur atau kutu yang dapat menyebabkanrasa gatal